Kidney Androgen-Regulated Protein (KAP) Transgenic Mice Are Protected Against High-Fat Diet Induced Metabolic Syndrome. Issue 1 (December 2017) - Quixano, Beatriz; Villena, Josep; Aranda, Miguel; Brils, Gemma; Cuevas, Antoni; Hespel, Théana; Lekuona, Haizea; Súarez, Cristina; Tornavaca, Olga; Meseguer, Anna
Abstract Metabolic Syndrome (MS) is reaching epidemic proportions with significant social and economical burden worldwide. Since the molecular basis of MS remains poorly defined, we investigated the impact of KAP, a kidney specific androgen-regulated gene, in the development of high fat-diet (hfd)-induced MS. Tg mice overexpressing KAP specifically in proximal tubule cells of the kidney exhibited reduced body weight and lower liver and adipose tissue weight compared to control littermates when fed a hfd. KAP Tg mice showed diminished adipocyte hypertrophy and reduced hepatic steatosis, significantly correlating with expression of relevant molecular markers and lower lipid content in liver. KAP transgenic were protected from hfd-induced insulin resistance, increased blood pressure and exhibited lower IL-6 serum levels and diminished expression of inflammatory markers in the adipose. Moreover, KAP was localized in the secretory pathway of proximal tubule cells and it is released to the extracellular media, preventing IL-6 induction and STAT-3 activation upon TNFα stimulation. We conclude that KAP, which might act as a hormone-like product in extra-renal tissues, protects Tg mice against hfd-induced MS by preventing inflammatory related events that are mediated, in part, through the IL-6 pathway.